The Effect of Digital Transformation on The Business Strategy of SMEs in The City of Bandung - Zahra Putri Khoerunsiya; Tina Yustiana; Alda Sofyana; Abi Sopyan Febrianto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
Penelitian ini Changes are driven by technological developments in organizations and work environments. Business competition today is very strict, and it must be able to meet the needs and desires of consumers. One of the best efforts is to follow up with technological change or transform into digital by using digital technology in a business strategy. The aim of this research is to understand the impact of digital transformation and the use of technology on UMKM's business strategy. This research is a type of descriptive qualitative research; data collection is carried out through interviews with UMKM perpetrators in the city of Bandung who use social media for both operational activities and sales and marketing. Interviews are conducted through WhatsApp and Instagram. The results obtained from this research are that digital transformation affects the business strategy of UMKM in Bandung; the presence of digital transformation makes UMKM actors use the strategy by creating content that is consistently interesting, not doing hard selling, understanding fan marketing, and leveraging the existence of influencers or celebrities.